Business Cycle Extraction of Euro-Zone GDP: Direct versus Indirect Approach - Roberto Astolfi; Dominique Ladiray; Gian Luigi Mazzi (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
Most of the Euro-zone economic short-term indicators are computed through aggregation from Member States data. The seasonally adjusted figures can be calculated by seasonally adjusting the aggregate (direct approach) or aggregating the seasonally adjusted national data (indirect approach). Statistical and practical considerations to choose the right strategy are given in the paper. An application to the Euro-zone GDP is presented. The same aggregation problem encountered in the case of seasonal adjustment will persist when extracting the business cycle. Moreover, since raw figures imply problems in terms of excessive noise of the series, analysts generally prefer the use of seasonally adjusted time series. As a consequence, the problem of choosing between direct and indirect both in seasonal adjustment and in business cycle extraction appears to be closely linked. In fact, the approach chosen to seasonally adjust the data can in theory lead to different results when the cyclical component has to be extracted from sea-sonally adjusted data. After a review of different filters widely used in the literature, we extracted the cycle indicator for the Euro-zone employing the Baxter-King filter to data coming from both direct and indirect seasonally adjustment approach and then compared the relative results.
Keywords: 330; Nationaleinkommen; Konjunktur; Konjunkturindikator; Aggregation; Statistische Methode; Eurozone; EU-Staaten; Saisonbereinigung